TRADISI MENGEMIS: PERGULATAN ANTARA EKONOMI DAN AGAMA: Studi Perilaku Mengemis Masyarakat di Demak - Saleh, Khairul; Riyanto, Riyanto; Mustaqim, Muhamad (LP2M IAIN kUDUS, 2014)
Abstract THE TRADITION OF BEGGING: STRIFE BETWEEN ECONOMICS AND RELIGION (THE STUDY OF SOCIETY BEGGING BEHAVIOR IN DEMAK). This paper is the result of a research about the begging behavior which has been done by the villagers of village Asinan, Demak. Perpetrators of begging or known by the term “wama-wama” generally were affected by economic and religious motifs. This economic motivation deals with how to earn money easily, spend few modal as well as capital gain. While religious motivations related to the perception of the perpetrators who believe that what they do is part of the rituals of the religion. In terms of the mode and form of behavior “wama-wama” varies, as accompany a mosque dome in a process, using city kamal, bring proposals and envelope models. But in general that is widely used is a proposal model. The mode is bringing a proposal of mosque and boarding school building. They deposit an amount of money that has been determined by the organizers, while the rest was the right of the offender.